Distinguishing various influences on the electrical properties of thin-barrier AlGaN/GaN heterojunctions with in-situ SiNx caps. (September 2021) - He, Jiaqi; Cheng, Wei-Chih; Jiang, Yang; Fan, Mengya; Zhou, Guangnan; Yang, Gaiying; Jiang, Lingli; Wang, Xiang; Wu, Zhanxia; Wang, Qing; Yu, Hongyu
Abstract: Understanding the individual contributions of the factors that influence the electrical properties of a material is important for controlling these properties. In this study, the effects of multiple factors on the electrical properties of thin-barrier AlGaN/GaN heterojunctions with in-situ SiN x caps were investigated using step etching and annealing treatments. The sheet density of the two-dimensional electron gas decreased by 5.9% and 29.5% due to the decrease in the piezoelectric polarization of the AlGaN barrier and the variations in interface charges during SiN x removal, respectively, and it recovered greatly by 72% after annealing-induced surface reconstruction. Capacitance-voltage results clearly revealed few interface traps on the heterojunction with the in-situ SiN x cap. Moreover, a maximum output current of 705 mA/mm and threshold voltage hysteresis below 50 mV were achieved by optimizing the in-situ SiN x interlayer on a thin-barrier metal-insulator-semiconductor structure. This study presents an efficient method for modulating the properties of two-dimensional electron gas and provides insights into the functionality of in-situ SiN x passivation on thin-barrier AlGaN/GaN heterojunctions.